Timescale of magma chamber processes revealed by U–Pb ages, trace element contents and morphology of zircons from the Ishizuchi caldera, Southwest Japan Arc. (22nd February 2017) - Takehara, Mami; Horie, Kenji; Tani, Kenichiro; Yoshida, Takeyoshi; Hokada, Tomokazu; Kiyokawa, Shoichi
Abstract: U–Pb geochronology and trace element chemistry of zircons in a microscale analysis were applied to the Ishizuchi caldera in the Outer Zone of Southwest Japan in order to estimate the timescale of the magma process, in particular, the magma differentiation. This caldera is composed mainly of ring fault complexes, major pyroclastic flow deposits, and felsic intrusion including central plutons. Using SHRIMP‐IIe, our new U–Pb zircon ages obtained from the major pyroclastic flow deposits (Tengudake pyroclastic flow deposits), granitic rocks from central plutons (Soushikei granodiorite and Teppoishigawa quartz monzonite), and rhyolite from the outer ring dike (Tenchuseki rhyolite) and the inner ring dike (Bansyodani rhyolite) are 14.80 ±0.11 Ma, 14.56 ±0.10 Ma, 14.53 ±0.12 Ma, 14.55 ±0.11 Ma and 14.21 ±0.19 Ma, respectively. Based on the U–Pb ages, the Hf contents and the REE patterns of the zircons, three stages are recognized in the evolutionary history of the magma chamber beneath the Ishizuchi caldera: (i) climactic Tengudake pyroclastic flow eruption; (ii) Tenchuseki rhyolite intrusion into the outer ring dike and central pluton intrusion; and (iii) Bansyodani rhyolite intrusion in the inner ring dike. These results indicate a magma evolution history of the Ishizuchi caldera system which took at least ca  600 kyr from the climatic caldera‐forming eruption to the post‐caldera intrusions. Our new geochronological data suggest that the Ishizuchi caldera formed as part of the voluminous and episodic magmatism that occurred in the wide zone along the Miocene forearc basin of Southwest Japan during the inception of the young Philippine Sea Plate subduction. Abstract : U–Pb geochronology and trace element chemistry of zircons in a microscale analysis were applied to the Ishizuchi caldera in the Outer Zone of Southwest Japan in order to estimate the timescale of the magma process, in particular, the magma differentiation. Based on the U–Pb ages, the Hf contents and the REE patterns of the zircons, three stages are recognized in the evolutionary history of the magma chamber beneath the Ishizuchi caldera: (i) climactic Tengudake pyroclastic flow eruption; (ii) Tenchuseki rhyolite intrusion into the outer ring dike and central pluton intrusion; and (iii) Bansyodani rhyolite intrusion in the inner ring dike. These results indicate a magma evolution history of the Ishizuchi caldera system which took at least ca 600 kyr from the climatic caldera‐forming eruption to the post‐caldera intrusions.